The Role of Context in Teaching English to the Speakers of Other Languages (TESOL) - Kabir, Md Humayun (IIUC Studies, 2012)
In this article, we have tried to develop a clear concept of approach i.e.-language theory and learning theory and also presented the idea of method i.e. - a way of teaching a language which is based on systematic principles and procedures. Subsequently, we have tried to clarify the notion of context. In the discussion, I have attempted to explain why the consideration of contextual factors is vitally important in applying an approach or method by a language teacher while she/he teaches. I have also examined and given references to the context of my teaching experience in Bangladesh which are relevant to the thesis of this article. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12256 IIUC Studies Vol.7 2011: 25-36